Digital Training From Home (DFH) For Teachers At SD KKG Reje Lele Nimbong Cibal District : Digital From Home dalam Pembelajaran Daring; 2;KKG. - Yuliana Wahyu; Heribertus Padova Jelamu; Marselina Herlinda Sriyati; Maksimilianus Nike (Universitas Serang Raya, 2022)
This PKM departs from the many problems of online learning during the current COVID-19 pandemic. This PKM is carried out to train and assist teachers in using technology-based learning applications, namely Google Classroom, Google Form, Google Meet, and Zoom. The choice of LMS types such as Google Classroom, Google Form, Google Meet, and Zoom are considered easy to use by teachers and by students. Google classroom by integrating various features used, namely google form (to provide questions/practices during the learning process), google meet (for face-to-face learning online), google drive, google doc., and so on. This PKM is carried out for teachers in the Reje catfish Nimbong KKG cluster in Cibal sub-district. KKG (Teacher Working Group) as a forum for teachers to develop their professionalism through training, seminars, sharing, about new learning information, the use of updated learning media and learning evaluation and assessment techniques. Based on this consideration, this digital from home training was conducted at the Reje Lele Nimbong KKG, Cibal District.